AN ANALYSIS OF SYNTAX ERRORS IN DESCRIPTIVE ESSAYS - Farah Zulfiah (Department of Master of Linguistic, Universitas Airlangga, 2020)
This research was conducted to analyze the syntax error. The object of this research is a descriptive essay for English education students batch 2019 which was made during the second semester. The author's aim in this study is to analyze the existence of syntax errors and the types of errors in writing descriptive essays. In this study, the author uses a qualitative descriptive method. The results of the research in the findings and discussion section stated that the descriptive essays of English education students in class 2019 stated that there were a number of syntax errors. In the finding section, the writer found eleven types of syntax error sentences in three student descriptive essays. From eleven example sentences, the writer finds the location of errors in the structure of phrases, clauses, and sentences. And from the three error syntax areas, two types of syntax errors were found by students, there are omission and addition. The most syntax errors are phrase structure errors in omission and the smallest is clause errors in the ‘Wh’ question. Many sentence errors in omission because incorrect because there is no verb in the clause. Each clause needs a subject and a verb. In some cases, the best verb to use is a simple is or was (or some other form of the verb to be). Keywords: error analysis, syntax error, descriptive essay.